Efektivitas Surat Somasi Dalam Penyelesaian Sengketa Perdata Secara Non-Litigasi - Keisha Anakku Putri Silalahi; Herlina Manullang (Judge : Jurnal Hukum, 2025)
Legal notice is the first step in resolving civil disputes through non-litigation. A formal notice serves as a written warning from the creditor to the debtor to correct their mistake or negligence before the case is brought to court if the formal notice is ignored based on Article 1238 of the Civil Code and the principle of good faith in Article 1338 paragraph (3) of the Civil Code. This study aims to analyze the extent to which legal notice plays a role in non-litigious civil dispute resolution and the extent to which legal notice accelerates the civil dispute resolution process. This study uses a normative juridical approach by examining the written legal norms that apply in the positive legal system in Indonesia, as well as considering the legal principles and doctrines of legal experts relevant to the issues under study. The results of the study show that legal notice has a significant psychological, moral, and procedural impact, as it can foster legal awareness, encourage voluntary compliance, and accelerate dispute resolution without having to go through litigation. Thus, legal notice plays a strategic role as a legal instrument that supports effective, efficient, and socially just dispute resolution.